2011
DOI: 10.1016/j.biortech.2011.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Active heterotrophic biomass and sludge retention time (SRT) as determining factors for biodegradation kinetics of pharmaceuticals in activated sludge

Abstract: a b s t r a c tThe present study investigates the biodegradation of pharmaceutically active compounds (PhACs) by active biomass in activated sludge. Active heterotrophs (X bh ) which are known to govern COD removal are suggested as a determining factor for biological PhAC removal as well. Biodegradation kinetics of five polar PhACs were determined in activated sludge of two wastewater treatment plants which differed in size, layout and sludge retention time (SRT).Results showed that active fractions of the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 27 publications
(34 reference statements)
8
40
1
Order By: Relevance
“…This is not the first time showing this correlation, since other authors observed a similar behavior in lab scale reactors or activated sludge units in STPs (Clara et al, 2005;Lishman et al, 2006), but the disparity on the reported removal efficiencies for this compound no matter if aerobic, anoxic or anaerobic conditions are present (Carballa et al, 2007b;Ternes et al, 2007;Suarez et al, 2010) makes difficult to outline clear conclusions. On the contrary, although no clear correlation was found, biodegradation rates and kinetic constants of most compounds decreased at higher SRTs, as previously observed by Majewsky et al (2011).…”
Section: Sludge Retention Timesupporting
confidence: 68%
“…This is not the first time showing this correlation, since other authors observed a similar behavior in lab scale reactors or activated sludge units in STPs (Clara et al, 2005;Lishman et al, 2006), but the disparity on the reported removal efficiencies for this compound no matter if aerobic, anoxic or anaerobic conditions are present (Carballa et al, 2007b;Ternes et al, 2007;Suarez et al, 2010) makes difficult to outline clear conclusions. On the contrary, although no clear correlation was found, biodegradation rates and kinetic constants of most compounds decreased at higher SRTs, as previously observed by Majewsky et al (2011).…”
Section: Sludge Retention Timesupporting
confidence: 68%
“…In order to avoid biased estimates and negative elimination efficiencies, the use of a sampling strategy that takes into consideration the hydraulic residence time distribution of WWTPs has been proposed (Majewsky et al 2011a). While the differences in the microbial communities of AS systems can lead to variable SMX removals, the active fraction of AS has also been shown to impact the biodegradation of SMX in full-scale systems and should be considered in future studies (Majewsky et al 2011b). The first batch test used samples of river sediment (3 g dry weight) and river water (60 mL) spiked with 20 μg/L SMX and resulted in 10 % SMX degradation after 30 days (~25 h half-life); this increased to 22 % removal in the presence of methanol, which served as an added carbon source (~10 h half-life) (Radke et al 2009).…”
Section: Removal In Full-scale Wwtps Based On Asmentioning
confidence: 99%
“…[5][6][7] Furthermore, caffeine generates demethylated products because of biodegradation by human metabolism and microbial biodegradation. 8,9 Biodegradation has so far been the main process involved in the removal of caffeine during activated sludge treatment, 10 and demethylation is expected to be the main pathway. Firstly, theophylline, paraxanthine and theobromine are formed by oxidative demethylation of caffeine.…”
Section: Introductionmentioning
confidence: 99%